Evidence of a secondary hypervolemia in trained man following acute high intensity exercise - Richardson, R. S.; Verstraete, D.; Johnson, S. C.; Luetkemeier, M. J.; Stray-Gundersen, J. (International Journal of Sports Medicine, 1996)
Exercise induced hypervolemia is well documented following the initial onset of chronic exercise. In trained man, however, it might be difficult to induce further PV expansion with exercise induced hypervolemia already present. Therefore the primary goal of this study was determine the effect of acute high intensity exercise on plasma volume (PV), cardiac output (CO), stroke volume (SV), heart rate (HR), and oxygen consumption (VO2), in fourteen male competitive runners (VO2max 60.7 +/- 6.4 ml.kg-1.min-1) in the middle of their season. In this well trained state, subjects twice performed three steady state runs at different speeds, and one maximal graded exercise test (baseline). After this baseline evaluation, subjects exercised at a high intensity (approximately 90-95% of VO2max) on 2 consecutive days (short-term high intensity STHI exercise). Subjects then repeated the submaximal runs and maximal exercise test (post high intensity exercise, PHIE). Following the intense exercise period, the subjects experienced an increase in PV of 4.4% (p < 0.05), HR was significantly reduced for any given running speed (p < 0.05) as was blood lactate concentration (p < 0.05), and SV was significantly increased by 4% (p < 0.05). Both CO and VO2 at submaximal running speeds were unaffected by the acute increase in exercise intensity. Maximal HR was also significantly reduced following the intense exercise (p < 0.05), but VO2max was unchanged. These data illustrate that STHI exercise can induce a secondary hypervolemia at a given work rate in trained man. These findings support scientific and anecdotal reports of a reduced HR response at a given work rate PHIE.